Antibacterial Activity and Solar UV-Protective Properties of Cotton Dyed with Natural Dye Compared with Commercial Yellow Robe - ศรีวิทยากูล วรวิทย์; รุ่งโรจนารักษ์ ธฤติ; ศรีมุณี ทวีป; มะแซ มาหามะสูไฮมี; ชูพูล ภาณุมาศ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The objective of this research was dyeing of cotton fabrics using Turmeric, Jackfruit wood and Sappan wood as a natural dye with Potassium aluminium sulfate (KAl(SO4)2.12H2O) as mordant. The color fastness to washing, perspiration and water of the dyed samples was determined according to AATCC test methods. In this study the UV-protection properties were investigated on cotton fabrics. Transmittance measurements were used to calculate the ultraviolet protection factor. The chemical functional groups of the dyes were characterized by using Fourier Transform Infrared Spectroscopy. Antibacterial activity of this dyed cotton was confirmed by exposing the fabric to Staphylococcus aureus and Escherichia coli reduced the number of viable organisms by 94 and 97 %. Cotton fabric dyed with turmeric, jackfruit wood and sappan wood had a yellow color look, like a yellow robe. Our results revealed that color fastness to washing, perspiration and water was fair to good level. The UV protection characteristics were also very good protection due to these extract composition of polyphenolic and tannin found in turmeric, Jack fruit wood and sappan wood. These extracts contained polyphenolic and tannin. Therefore, it was suggested that these extracts have potential in producing functional dyes that could be imparted into the yellow robe dyeing natural colourant system.